Temporal Changes in Vaginal Microbiota and Genital Tract Cytokines Among South African Women Treated for Bacterial Vaginosis - Mtshali, Andile; San, James Emmanuel; Osman, Farzana; Garrett, Nigel; Balle, Christina; Giandhari, Jennifer; Onywera, Harris; Mngomezulu, Khanyisile; Mzobe, Gugulethu; de Oliveira, Tulio; Rompalo, Anne; Mindel, Adrian; et al. (Frontiers in Immunology, 2021)
The standard treatment for bacterial vaginosis (BV) with oral metronidazole is often ineffective, and recurrence rates are high among African women. BV-associated anaerobes are closely associated with genital inflammation and HIV risk, which underscores the importance of understanding the interplay between vaginal microbiota and genital inflammation in response to treatment. In this cohort study, we therefore investigated the effects of metronidazole treatment on the vaginal microbiota and genital cytokines among symptomatic women with BV [defined as Nugent score (NS) ≥4] using 16S rRNA gene sequencing and multiplex bead arrays. Among 56 BV positive women, we observed short-term BV clearance (NS <4) proportions (30%, 17/56) six weeks after metronidazole treatment, with more than half (53%, 9/17) experiencing recurrence by 12 weeks post-treatment. Lactobacillus iners, BVAB1 and G. vaginalis dominant community state types (CSTs) were the most prevalent at baseline. Six weeks after treatment, the proportion of women with Lactobacillus iners-dominated CST increased from (27%, 15/56) to (39%, 22/56). BVAB1-dominant CST decreased from (30%, 17/56) to (20%, 11/56) and G. vaginalis-dominant CST decreased from (41%, 23/56) to (36%, 20/56) six weeks after treatment and the extent of the reduction continued at 12 weeks post-treatment. Using linear mixed model, BV clearance was associated with substantially decreased TNF-α (β= -2.450, p= 0.027), IL-1β (β= -2.234, p= 0.002), IL-8 (β= -2.214, p= 0.040), and LIF (β= -0.981, p= 0.043) concentrations, while BV persistence (NS ≥4) was associated with increased IL-1α (β= 0.466, p= 0.045), IL-18 (β= 0.621, p= 0.009), MIF (β= 0.481, p= 0.028), IL-7 (β= 0.363, p= 0.043), and LIF (β= 0.621, p= 0.038) concentrations. Concentrations of these cytokines were differentially regulated by changes in the relative abundance of BVAB1 and G. vaginalis. We conclude that metronidazole for the treatment of BV induced short-term shifts in the vaginal microbiota and mucosal cytokines, while treatment failures promoted persistent elevation of proinflammatory cytokine concentrations at the genital tract. Further mechanistic studies are needed to confirm this relationship between vaginal microbiota and genital inflammation, including how it affects women’s reproductive health and vulnerability to HIV infection.